Kajian Sosiolinguistik Alih Kode Terhadap “The Scheunemann, Keluarga Jerman yang Fasih Berbahasa Jawa” dalam Acara Hitam Putih - Ayu Winda Sari; Erni Erni (UIR Press, 2022)
Abstract Humans are individual creatures who cannot be separated from daily social interactions by using language. Individuals involved in language switching usually involve multilingual or multilinguistic matters. Therefore, in communicating, of course, code switching events are very possible. As in this study which raised the title